TWO NEW SPECIES OF POACEAE FROM INDIA - BHAT, K. GOPALAKRISHNA; NAGENDRAN, C. R. (Research Center for Biology, 1984)
Two new species of Poaceae namely, Erayrostis santapaui K. G. Bhat & C. R. Nagendran and Chrysopogon pseitdozeylanicus K. G. Bhat & C. R. Nagendran have been described from materials collected by the senior author from Coorg- and South Kanara Districts of Karnataka State, India.